What I did is just to talk; nothing else' : the experiences of HIV/AIDS counsellors attached to lifeline, Khayelitsha, Cape Town - Rohleder, Poul Andrew (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2003.